CEGAH STUNTING DENGAN PENGUATAN PERAN ORANG TUA BALITA DI SALAH SATU POSYANDU DI BINONG - Evanny Indah Manurung; Maria Veronika Ayu Florensa; Eva Chris Veronica Gultom; Marisa Junianti Manik; Shinta Yuliana Hasibuan; Veronica Paula; Melisa Constantine Sigarlaki; Winda Silaban S; Septa Meriana Lumbantoruan (JMM (Jurnal Masyarakat Mandiri), 2024)
Nutrition problems in toddlers are a major point in the growth and development of children under five. If the toddler's nutrition is not balanced, the toddler will suffer from stunting. One of the factors that causes is the lack of knowledge of mothers about stunting and balanced feeding in toddlers. The purpose of this Community Service is to strengthen the role of parents of toddlers in Poyandu Melati IV Binong in preventing stunting. The method used is to increase the knowledge of parents of toddlers through health education activities about fulfilling nutrition in toddlers and the role of parents in preventing stunting to 65 people who are mothers of toddlers who visit the posyandu. Based on the results of the evaluation conducted with the pretest and postest methods, there was an increase in the average answer value of 6.7 points with an average pretest value of 77.8 and a posttest of 84.5. This shows that the lecture education method is effective in improving knowledge.